2017
DOI: 10.1016/j.apcatb.2017.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-annealing induces sub-surface redox-states in surfactant-structured α-Fe2O3 photoanodes prepared by ink-jet printing

Abstract: Transparent nano-structured hematite (α-Fe2O3) films of approximately 550 nm thickness on tin-doped indium oxide (ITO) have been obtained conveniently by ink-jet printing of a Fe(NO3)3 / Brij® O10 precursor ink and subsequent annealing at 500 °C in air. When illuminated with a blue LED ( = 455 nm, ca. 100 mW cm -2 ), the hematite films exhibited photocurrents of up to 70 A cm -2 at 0.4 V vs. SCE in 0.1 M NaOH electrolyte. Thermal annealing in vacuum at 500 °C for 2 h increased photocurrents more than three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Then, it was found that it could be used as active site to improve the PEC performance. Oxygen vacancy appears in the special conditions like rapid thermal process (RTP) [28], which can bring about oxygen separation from the metaloxidation lattice [29]. Currently, oxygen vacancies are regarded as intrinsic defects and positive charges because of the strong electronegativity of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Then, it was found that it could be used as active site to improve the PEC performance. Oxygen vacancy appears in the special conditions like rapid thermal process (RTP) [28], which can bring about oxygen separation from the metaloxidation lattice [29]. Currently, oxygen vacancies are regarded as intrinsic defects and positive charges because of the strong electronegativity of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their behavioural characteristic of reducing surface tension at the water-air and oil-water interfaces, they are used widely in various industries as occulating and wetting agents, adhesives, inks, emulsiers and de-emulsiers and in the oil and gas industries. [1][2][3][4] However, most of the commercial synthetic surfactants have signicant detrimental effects on the environment, which has driven researchers to synthesize natural surfactants from renewable resources. [5][6][7] The focus on an eco-friendly environment concerns the use of surfactants and creates interest to develop a natural surfactant against commercial non-biodegradable surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…The anodic spike arises from charge separation and rapid electron diffusion toward/into the FTO−hematite interface. 27,28 The fast decay following the anodic spike is usually associated with slow oxygen evolution kinetics and the presence of surface traps (pseudocapacitance). Trap concentrations can be enhanced due to defects on the surface or in the crystal structure often associated with a low degree of crystallinity and purity of the hematite film.…”
mentioning
confidence: 99%